Investing in Indonesia's Education : Allocation, Equity, and Efficiency of Public Expenditures - Arze del Granado, F. Javier; Fengler, Wolfgang; Ragatz, Andy; Yavuz, Elif (World Bank, Washington, DC, 2012)
What are the current trends and main characteristics of public education spending in Indonesia? Is education spending insufficient? Are expenditures in education efficient and equitable? This study reports the first account of Indonesia's aggregated (national and sub-national) spending on education, as well as the economic composition of education spending and its breakdown by programs. It presents estimations of the expected (average) level of education spending for a country with its economic and social characteristics. This analysis sheds light on the efficiency and equity of education spending by presenting social rates of return by level of education, by assessing the adequacy of current teacher earnings relative to other paid workers and the distribution of teachers across urban, rural, and remote regions, and by identifying the main determinants of education enrollment. It concludes that the current challenges in Indonesia are no longer defined by the need of additional spending, but rather the need to improve the quality of education services, and to improve the efficiency of education expenditures by re-allocating teachers to undersupplied regions and re-adjusting the spending mix within and between education programs for future additional spending in the sector. The study finds that poverty and student-aged labor are also significant constraints to education enrollment, stressing the importance of policies aimed at addressing demand-side factors.